The use of calorimetry in the biophysical characterization of small molecule alkaloids binding to RNA structures - Kumar, Gopinatha Suresh; Basu, Anirban (Biochimica et biophysica acta, 2016)
RNA has now emerged as a potential target for therapeutic intervention. RNA targeted drug design requires detailed thermodynamic characterization that provides new insights into the interactions and this together with structural data, may be used in rational drug design. The use of calorimetry to characterize small molecule–RNA interactions has emerged as a reliable and sensitive tool after the recent advancements in biocalorimetry. This review summarizes the recent advancements in thermodynamic characterization of small molecules, particularly some natural alkaloids binding to various RNA structures. Thermodynamic characterization provides information that can supplement structural data leading to more effective drug development protocols. This review provides a concise report on the use of isothermal titration calorimetry (ITC) and differential scanning calorimetry (DSC) techniques in characterizing small molecules, mostly alkaloids–RNA interactions with particular reference to binding of tRNA, single stranded RNA, double stranded RNA, poly(A), triplex RNA. It is now apparent that a combination of structural and thermodynamic data is essential for rational design of specific RNA targeted drugs. Recent advancements in biocalorimetry instrumentation have led to detailed understanding of the thermodynamics of small molecules binding to various RNA structures paving the path for the development of many new natural and synthetic molecules as specific binders to various RNA structures. RNA targeted drug design, that remained unexplored, will immensely benefit from the calorimetric studies leading to the development of effective drugs for many diseases. This article is part of a Special Issue entitled Microcalorimetry in the BioSciences — Principles and Applications, edited by Fadi Bou-Abdallah. •The binding of small molecules to various RNA structures has been reviewed.•This review focuses on the interaction of alkaloids and dyes with RNA.•The use of ITC and DSC to characterize the binding phenomenon is presented.•The data on tRNA, ss RNA, ds RNA, poly(A) and triplex RNA has been reviewed.